Parvovirus B19 promoter at map unit 6 confers autonomous replication competence and erythroid specificity to adeno-associated virus 2 in primary human hematopoietic progenitor cells. - Wang, X S (1995)
The pathogenic human parvovirus B19 is an autonomously replicating virus with a remarkable tropism for human erythroid progenitor cells. Although the target cell specificity for B19 infection has been suggested to be mediated by the erythrocyte P-antigen receptor (globoside), a number of nonerythroid cells that express this receptor are nonpermissive for B19 replication. To directly test the role of expression from the B19 promoter at map unit 6 (B19p6) in the erythroid cell specificity of B19, we constructed a recombinant adeno-associated virus 2 (AAV), in which the authentic AAV promoter at map unit 5 (AAVp5) was replaced by the B19p6 promoter. Although the wild-type (wt) AAV requires a helper virus for its optimal replication, we hypothesized that inserting the B19p6 promoter in a recombinant AAV would permit autonomous viral replication, but only in erythroid progenitor cells. In this report, we provide evidence that the B19p6 promoter is necessary and sufficient to impart autonomous replication competence and erythroid specificity to AAV in primary human hematopoietic progenitor cells. Thus, expression from the B19p6 promoter plays an important role in post-P-antigen receptor erythroid-cell specificity of parvovirus B19. The AAV-B19 hybrid vector system may also prove to be useful in potential gene therapy of human hemoglobinopathies.